2022
DOI: 10.52965/001c.33921
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Update of Prolotherapy in the Management of Osteoarthritis of the Knee

Abstract: This is a comprehensive review of the literature focusing on the use of prolotherapy in the treatment of osteoarthritis of the knee. It covers the background, efficacy, and advantages of prolotherapy in the management of osteoarthritis symptoms and then covers the existing evidence of the use of prolotherapy for this purpose. Current treatments for osteoarthritis of the knee are numerous, yet patients continue to endorse chronic pain and poor quality of life. Prolotherapy is a treatment that has been inadequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…In addition, research has shown that dextrose solutions can stimulate the production of growth factors essential for the repair and growth of tendons, ligaments, and other soft tissues, indirectly supporting the idea of a prechondrogenic effect. It is important to note, however, that while the regenerative potential of dextrose in prolotherapy has been demonstrated, the claim of direct cartilage regeneration must be approached with caution 50,54,55 . The third hypothesis regarding the effect of prolotherapy is related to its modulating effect on pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, research has shown that dextrose solutions can stimulate the production of growth factors essential for the repair and growth of tendons, ligaments, and other soft tissues, indirectly supporting the idea of a prechondrogenic effect. It is important to note, however, that while the regenerative potential of dextrose in prolotherapy has been demonstrated, the claim of direct cartilage regeneration must be approached with caution 50,54,55 . The third hypothesis regarding the effect of prolotherapy is related to its modulating effect on pain.…”
Section: Discussionmentioning
confidence: 99%
“…While the precise mechanisms underlying these effects require further investigation, prolotherapy has shown promise as a therapeutic option for individuals with KOA. 20 , 27 , 49 , 50 , 51 Indeed, one of the hypotheses regarding the effect of prolotherapy on joints and tissues is that it promotes soft tissue proliferation, leading to tissue repair, recovery, and a reduction in edema and inflammation. Studies have demonstrated that dextrose 20% has a regenerative effect on healing damaged Achilles tendons by promoting fibroblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size of 20 achieves 81% power to detect a mean of paired differences of 0.7 with an estimated standard deviation of differences of 1.0 and with a significance level (alpha) of 0.05000 using a two-sided paired t-test. We assumed a dropout rate of 10%, then the recruited samples will be 15 samples [18,19].…”
Section: Discussionmentioning
confidence: 99%